An invitation to the dark side of economic geography. (February 2018) - Phelps, Nicholas A; Atienza, Miguel; Arias, Martin
This exchange urges economic geographers working within several major extant schools of thought to pay greater attention to uneven economic development in general and the dark side of the economic geographies in particular.